PENGARUH STRUKTUR MODAL, INTELLECTUAL CAPITAL, DAN KONSERVATISME AKUNTANSI TERHADAP KINERJA KEUANGAN - Seli Aprianti; Puspita Handayani (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the effect of Capital Structure, Intellectual Capital, and Accounting Conservatism on financial performance in Consumer Non-Cyclical Sector companies in the Food & Beverage sub-sector listed on the Indonesia Stock Exchange for the 2019-2024 period. The sampling method used in this study uses the Purposive Sampling method, with an associative quantitative research type. The data used are secondary data, namely the company's annual financial reports. The number of samples used in this study is 15 companies with observations for 6 (six) years, so that 90 observation objects were selected. The analysis technique uses the panel data regression method with the Eviews 12 application tool. The results of the study indicate that Capital Structure, Intellectual Capital, and Accounting Conservatism have a simultaneous effect on Financial Performance. Capital Structure has an effect on Financial Performance. Intellectual Capital has no effect on Financial Performance. Accounting Conservatism has no effect on Financial Performance.